The rules of interpretation: How do al-‘ām and al-khāş applied in Shihab’s exegesis? - Usman A.H.; Fattah M.; Amin M.F.M.; Abdullah W.N.W.; Othman F.M.; Kadir M.N.A. (Mediterranean Center of Social and Educational Research, 2024)
Indexed by Scopus